Mapping of Fabry–Perot and whispering gallery modes in GaN microwires by nonlinear imaging. (16th July 2021) - Berdnikov, Yury; Shtrom, Igor; Rozhavskaya, Maria; Lundin, Wsevolod; Hendricks, Nicholas; Grange, Rachel; Timofeeva, Maria
Abstract: Engineering nonlinear optical responses at the microscale is a key topic in photonics for achieving efficient frequency conversion and light manipulation. Gallium nitride (GaN) is a promising semiconductor material for integrated nonlinear photonic structures. In this work, we use epitaxially grown GaN microwires as nonlinear optical whispering gallery and Fabry–Perot resonators. We demonstrate an effective generation of second-harmonic and polarization-dependent signals of whispering gallery and Fabry–Perot modes (FPM) under near-infrared (NIR) excitation. We show how the rotation of the excitation polarization can be used to control and switch between Fabry–Perot and whispering gallery modes in tapered GaN microwire resonators. We demonstrate the enhancement of two-photon luminescence in the yellow-green spectral range due to efficient coupling between whispering gallery, FPM, and excitonic states in GaN. This luminescence enhancement allows us to conveniently visualize whispering gallery modes excited with a NIR source. Such microwire resonators can be used as compact microlasers or sensing elements in photonic sensors.